Isothermal and temperature-cycling retrogradation of high-amylose corn starch: Impact of sonication on its structural and retrogradation properties - Kyu Tae Han; Ha Ram Kim; Tae Wha Moon; Seung Jun Choi (Ultrasonics Sonochemistry, 2021)
In this study, the effects of sonication and temperature-cycled storage on the structural properties and resistant starch content of high-amylose corn starch were investigated. Sonication induced a partial depolymerization of the molecular structures of amylopectin and amylose. Sonication treatment induced the appropriate structural changes for retrogradation. Although the relative crystallinity of sonicated starch was lower than that of non-sonicated starch, sonicated starch after retrogradation showed much higher relative crystallinity than non-sonicated starch. Regardless of sonication treatment, temperature-cycled storage resulted in a higher degree of retrogradation than isothermal storage, but the rate of retrogradation was greater in sonicated starch than in non-sonicated starch, as supported by retrogradation enthalpy, the Avrami constant, and relative crystallinity. The highly developed crystalline structure in sonicated starches due to retrogradation was reflected by the large amount of resistant starch.